2013
DOI: 10.1002/j.2055-2335.2013.tb00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Compounding Practices in Queensland: Experiences and Perceptions of Pharmacists and Pharmacy Students

Abstract: Background Changes in the roles of the contemporary pharmacist has seen a decline in the number and variety of extemporaneously compounded dosage forms. Pharmacy curricula reflect this change with a reduction in the emphasis on extemporaneous compounding practice. Aim To elicit information about extemporaneously compounded dosage forms and perceptions of compounding practice from pharmacists and pharmacy students. Method Self‐administered surveys were mailed to 1063 pharmacists and offered online to 896 pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The majority of evidence relating to compounding includes only pharmacy students at metropolitan universities. 34 This study, however, includes students from pharmacy, medicine, dentistry, and allied health disciplines from both metropolitan and regional universities and thus gives credibility to our findings.…”
Section: Discussionsupporting
confidence: 58%
“…The majority of evidence relating to compounding includes only pharmacy students at metropolitan universities. 34 This study, however, includes students from pharmacy, medicine, dentistry, and allied health disciplines from both metropolitan and regional universities and thus gives credibility to our findings.…”
Section: Discussionsupporting
confidence: 58%
“…Compounding can be defined as combining, admixing, diluting, reconstituting, or otherwise altering a drug or bulk drug substance to create a desired medication. 12 , 13 Most commercially available medicines are formulated as solid dosage forms and may not be in the desired strength and dosage forms to meet specific patient needs particularly for dermatological complications. 10 , 14 Buurma et al reported that dermatological dosage forms accounted a significant share (62.1%) among compounded medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The authors raised some concerns in relation to the curriculum, such as a lack of transforming the learned content into practice, differences between the equipment used in the university laboratory compared to the community pharmacy, and a decreased confidence of final-year students due to a time gap since their last compounding class. Furthermore, the authors explained that after the findings of this study they had revised their curriculum in regard to compounding training [4]. The obstacles observed by the research team can be tackled during the internship year which is a compulsory part of becoming a registered pharmacist.…”
Section: Discussionmentioning
confidence: 98%
“…In Australia, the pharmacy curricula have been progressively adjusted to address the new challenges that pharmacists are facing [2]. Nevertheless, it should be acknowledged that pharmacies are still offering compounding services which require the pharmacists to be also equipped with this set of skills [3,4].…”
Section: Introductionmentioning
confidence: 99%